A method and plasma device for realizing resource utilization by treating solid waste plastics with plasma
By filling solid dielectric spheres in the plasma reactor to pretreat the plastic, the problem of pyrolysis product distribution regulation is solved, the yield of gaseous hydrocarbon products such as methane, ethane, propane, and ethylene is significantly improved, and waste is achieved Efficient resource utilization of plastics.
Patent Information
- Application Number
- CN202411258883.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The existing pyrolysis methods cannot effectively regulate the distribution of plastic pyrolysis products, resulting in the difficulty of improving the economic value of waste plastics.
Using a dielectric barrier discharge plasma reactor, solid waste plastic is pretreated by filling the discharge cavity with solid dielectric spheres, increasing its surface functional groups, low polymerization and crystallinity, and then pyrolysis is performed to generate High-value gaseous hydrocarbon products.
The output of high-value gaseous hydrocarbon products in the pyrolysis products has been improved, and the efficient and value-added resource utilization of solid waste plastics has been achieved.
Smart Images

Figure CN118768364B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of resource recovery of solid waste plastics, and specifically relates to a method for recovering solid waste plastics by plasma treatment and a plasma device. Background Art
[0002] Plastics have many unique properties, such as low cost, durability, safety, processability, and huge chemical diversity that can be customized to meet various specific application requirements. These properties have led to an ever-expanding range of applications for plastics in the global economy. The rapid growth in demand for plastics has significantly increased their production. However, most waste plastics are not properly handled, resulting in resource waste and environmental pollution. The production of plastics mainly relies on petroleum resources, and recycling and upgrading waste plastics into fuels and other high-value chemicals is a promising solution. Compared with mechanical recycling methods represented by reprocessing, thermochemical treatment methods such as gasification and pyrolysis can effectively convert waste plastics, thereby achieving value-added utilization of waste plastics. Pyrolysis refers to the process of destroying polymer molecular chains at high temperatures in an oxygen-free environment, converting them into small molecular products mainly composed of hydrocarbons, including alkanes, cycloalkanes, and aromatics. Since plastics are products of the petrochemical industry, converting them into petroleum fractions or other petrochemical products through pyrolysis undoubtedly has a higher atomic utilization efficiency. However, the current pyrolysis method cannot achieve the regulation of the distribution of plastic pyrolysis products, making it difficult to improve the economic value of plastic pyrolysis products. Summary of the invention
[0003] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for recycling solid waste plastics by plasma treatment.
[0004] The present invention adopts a dielectric barrier discharge plasma reactor in which a discharge cavity is filled with solid dielectric spheres and other solids to perform plasma pretreatment on solid waste plastics, so that the solid waste plastics contain rich surface functional groups, low polymerization degree, high crystallinity and rough surface morphology; then pyrolysis is performed to make the pyrolysis products move toward the low molecular weight range, and a large amount of methane, ethane, propane, ethylene and propylene substances are obtained, thereby increasing the output of high-value gaseous hydrocarbon products in the pyrolysis products, and realizing efficient and value-added resource utilization of solid waste plastics.
[0005] Another object of the present invention is to provide a dielectric barrier discharge plasma reaction device. The device performs plasma pretreatment on solid waste plastics by filling solid dielectric spheres in the discharge cavity. Compared with a dielectric barrier discharge plasma reaction device in which the discharge cavity is not filled with solid dielectric spheres, the solid dielectric spheres can make the solid waste plastics have more abundant surface functional groups, lower polymerization degree, higher crystallinity and rough surface morphology, and the yield of high-value gaseous hydrocarbon products obtained after pyrolysis is greater.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A method for recycling solid waste plastics by plasma treatment comprises the following steps:
[0008] (1) Placing plastic particles in a discharge cavity of a dielectric barrier discharge plasma reaction device, performing carrier gas purge at room temperature, and then performing plasma treatment to obtain plasma-treated plastic particles;
[0009] The discharge cavity of the dielectric barrier discharge plasma reaction device is filled with solid dielectric balls;
[0010] (2) In an inert gas atmosphere, the plasma-treated plastic particles are pyrolyzed to obtain a mixed product containing gaseous hydrocarbons, thereby realizing the resource utilization of solid waste plastics.
[0011] Preferably, the plastic in step (1) is a general-purpose plastic, specifically at least one of PVC, PE, PP, PS and ABS.
[0012] More preferably, the plastic in step (1) is high-density polyethylene.
[0013] Preferably, the plastic particles in step (1) are cleaned, crushed and sieved before plasma treatment; the sieving is to 20-100 mesh, more preferably 40-60 mesh.
[0014] Preferably, the dielectric barrier discharge plasma reaction device in step (1) is a dielectric barrier discharge plasma reactor with a double-layer dielectric flat plate structure.
[0015] Preferably, the depth of the discharge cavity of the dielectric barrier discharge plasma reaction device in step (1) is 6 to 20 mm, and the interior is filled with solid dielectric spheres to enhance plasma discharge, and the diameter of the solid dielectric spheres is greater than 2 mm and less than the depth of the discharge cavity.
[0016] Preferably, the material of the solid dielectric sphere in step (1) is at least one of chemically inert ceramics and glass; more preferably at least one of alumina ceramics, zirconia ceramics, barium titanate ceramics and quartz glass.
[0017] Preferably, the carrier gas in step (1) is an inert gas, more preferably at least one of argon, helium and nitrogen.
[0018] Preferably, the conditions for the plasma treatment in step (1) are: a discharge power of 5 to 100 W, a carrier gas flow rate of 50 to 100 mL / min, and a plasma treatment time of 5 minutes to 3 hours.
[0019] More preferably, the conditions for the plasma treatment in step (1) are: a discharge power of 20 W, a carrier gas flow rate of 50 mL / min, and a plasma treatment time of 1 hour.
[0020] The dielectric barrier discharge plasma reaction device in step (1) is a double-layer dielectric flat plate structure dielectric barrier discharge plasma reactor, and the present invention only fills its discharge cavity with solid dielectric balls.
[0021] The plastic particles treated by plasma in step (1) have irregular surface morphology, abundant surface functional groups, high crystallinity and low degree of polymerization.
[0022] Preferably, the inert gas in step (2) is at least one of argon, helium and nitrogen.
[0023] Preferably, the pyrolysis conditions in step (2) are: a carrier gas flow rate of 100 to 500 mL / min, a temperature of 500 to 800 °C, and a pyrolysis time of 1 to 30 minutes.
[0024] More preferably, the pyrolysis conditions in step (2) are: a carrier gas flow rate of 156 mL / min and a temperature of 600-800°C.
[0025] Preferably, after pyrolysis in step (2), a mixed product containing gaseous hydrocarbons is obtained, which is further heated and catalytically converted into hydrogen under the action of a catalyst.
[0026] More preferably, the temperature of the heating catalysis is 800-1000°C, and the catalyst is a FeNi / Al2O3 supported catalyst.
[0027] By adopting the above-mentioned method of plasma treatment of solid waste plastics to realize resource recovery, the plasma can realize strong discharge in the inert gas and cover the plastic particles located in the plasma discharge chamber, ensuring that the plastic is fully exposed to the plasma and modified.
[0028] A dielectric barrier discharge plasma reaction device comprises a shell that penetrates from top to bottom, a solid dielectric ball, an air inlet, an air outlet, a first electrode plate, a second electrode plate, a first dielectric plate and a second dielectric plate;
[0029] The shell is through-through, with a first dielectric plate on the top and a second dielectric plate on the bottom. The cavity formed by the shell, the first dielectric plate and the second dielectric plate is a discharge cavity. The solid dielectric ball is filled in the discharge cavity.
[0030] The air inlet and the air outlet are located on both sides of the shell;
[0031] The first electrode plate is attached above the first dielectric plate, and the second electrode plate is attached below the second dielectric plate.
[0032] Preferably, the dielectric barrier discharge plasma reaction device further includes an upper cover and a lower end cover; the upper cover is sleeved on the outside of the first electrode plate and screwed to the top of the shell, tightly pressing and fixing the first dielectric plate between the shell and the first electrode plate; the lower end cover is sleeved on the outside of the second electrode plate and screwed to the bottom of the shell, tightly pressing and fixing the second dielectric plate between the shell and the second electrode plate.
[0033] Preferably, the dielectric barrier discharge plasma reaction device further includes upper and lower brackets; the upper bracket is connected and fixed above the first electrode plate, and the lower bracket is connected and fixed below the second electrode plate.
[0034] More preferably, in the dielectric barrier discharge plasma reaction device, the upper and lower brackets are correspondingly provided with screw holes, and the upper and lower brackets are fastened by bolts to clamp and fix the dielectric barrier discharge plasma reaction device.
[0035] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0036] The present invention obtains a solid waste plastic sample with rich surface functional groups, low polymerization degree and high crystallinity through plasma treatment. The plastic sample has a high concentration of carbonyl and methylene functional groups, a rough surface morphology of scales or sponges, a low polymerization degree and a high crystallinity, which is conducive to deep dissociation during the pyrolysis process to promote the distribution of pyrolysis products to move toward the low molecular weight category, produce a large amount of methane, ethane, propane, ethylene and propylene substances, and increase the yield of high-value gaseous hydrocarbon products in the pyrolysis products; or further introduce a catalyst for catalytic conversion to produce hydrogen, thereby further improving the utilization rate of plastic pyrolysis products and their economic value, and realizing efficient and value-added resource utilization of solid waste plastics. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a scanning electron microscope image of an untreated plastic particle in Comparative Example 1 of the present invention at a resolution of 1 μm;
[0038] Figure 2 This is a scanning electron microscope image of a plastic particle treated with argon plasma at a resolution of 1 μm in Example 1 of the present invention;
[0039] Figure 3 This is a scanning electron microscope image of a plastic particle treated with helium plasma at a resolution of 1 μm in Example 2 of the present invention;
[0040] Figure 4 This is a Fourier transform infrared spectrum comparison diagram of a plastic particle treated with argon plasma and a plastic particle not treated with plasma in Example 1 of the present invention;
[0041] Figure 5 This is a Fourier transform infrared spectrum comparison diagram of a plastic particle treated with helium plasma and a plastic particle not treated with plasma in Example 2 of the present invention;
[0042] Figure 6 This is a comparison diagram of heat flow curves of plastic particles treated with argon plasma and untreated plastic particles in Example 1 of the present invention;
[0043] Figure 7 This is a comparison diagram of heat flow curves of plastic particles treated with helium plasma and untreated plastic particles in Example 2 of the present invention;
[0044] Figure 8 This is a comparison diagram of molecular weight distribution curves of plastic particles treated with argon plasma and untreated plastic particles in Example 1 of the present invention;
[0045] Fig. 9 It is a schematic diagram of a dielectric barrier discharge plasma reaction device;
[0046] Among them, 1 is the upper bracket of the reaction device, 2 is the positive electrode (first electrode plate), 3 is the upper cover of the reaction device, 4 is the first quartz glass dielectric plate, 5 is the dielectric ball, 6 is the shell of the reaction device, 7 is the second quartz glass dielectric plate; 8 is the lower end cover of the reaction device, 9 is the grounding electrode (second electrode plate), 10 is the lower bracket of the reaction device, 11 is the air inlet sealing cover, 12 is the air outlet sealing cover, and 13 is the fastening bolt;
[0047] Fig.10 The voltage-current waveform diagram of the plasma discharge process when Example 1 of the present invention is filled with quartz glass balls with a diameter of 4 mm and when Comparative Example 3 is not filled with dielectric balls. DETAILED DESCRIPTION
[0048] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0049] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0050] The weight of the relevant components mentioned in the examples of the present application can not only refer to the specific content of each component, but also indicate the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the examples of the present application, it is within the scope disclosed in the description of the examples of the present application. Specifically, the mass described in the description of the examples of the present application can be a mass unit known in the chemical industry such as µg, mg, g, kg, etc.
[0051] The FeNi / Al2O3 supported catalyst described in the following examples and comparative examples is prepared as follows: First, 7.054 g of ferric nitrate nine hydrate and 5.077 g of nickel nitrate hexahydrate are fully stirred and dissolved in 100 mL of deionized water to prepare a metal salt solution. The prepared metal salt solution is added to 8 g of γ-Al2O3 powder, stirred at room temperature for 1 hour, transferred to a water bath, and stirred and evaporated at 80°C. Subsequently, the dried sample is transferred to an oven and dried at 110°C overnight. The sample is then calcined at 550°C in a muffle furnace for 4 hours and cooled naturally after calcination. The calcined sample is crushed and sieved to 40-60 mesh. Before use, the catalyst is reduced at 800°C for 1.5 hours in a mixed gas containing 10vol.% H2-He at a gas flow rate of 100 mL / min in a tubular furnace. The metal salts used to prepare the catalyst are ferric nitrate nonahydrate (brand: Aladdin, item number: F100208, CAS number: 7782-61-8), nickel nitrate hexahydrate (brand: Aladdin, item number: N108893, CAS number: 13478-00-7), and the alumina powder is γ-phase alumina (brand: Aladdin, item number: A102091, CAS number: 1344-28-1).
[0052] The dielectric barrier discharge plasma reactors described in Examples 1 to 6 and Comparative Example 3 are all conventional double-layer dielectric flat plate structure dielectric barrier discharge plasma reactors. The only difference between the dielectric barrier discharge plasma reactors described in Examples 1 to 6 and Comparative Example 3 is that the discharge cavity of Examples 1 to 6 is filled with quartz glass balls with a diameter of 4 mm to fill the discharge space, while Comparative Example 3 is not filled.
[0053] Example 1
[0054] A method for pretreating solid plastics by argon plasma to increase the yield of gaseous hydrocarbon pyrolysis products and realize resource utilization, comprising the following steps:
[0055] Commercial high-density polyethylene particles (brand: McLean, CAS number: 9002-88-4, item number: H875017) were sieved to obtain high-density polyethylene particles of 60-80 mesh. They were placed in a constant temperature oven and dried at 80 °C for 10 hours. 2 g of dry high-density polyethylene particles were weighed and placed in the plasma discharge cavity (depth of 6 mm) of the dielectric barrier discharge plasma reactor, and filled with quartz glass balls with a diameter of 4 mm until the discharge space was filled. After the reactor was sealed, argon was introduced as a carrier gas, and the plasma power was turned on after purging at a flow rate of 50 mL / min for 30 minutes. The plasma discharge power was adjusted to 20 W by the Lissajous figure method and the treatment was continued for 1 hour to obtain plasma-treated high-density polyethylene particles. The plasma-treated high-density polyethylene particles were further pyrolyzed and their pyrolysis products were detected. The pyrolysis and detection conditions were described in the "Performance Test Experiment" section.
[0056] The characterization results of the plastic particles obtained after the plasma pretreatment in the above steps show that the morphology and structure of Example 1 are as follows: Figure 2 As shown, compared with the untreated plastic sample ( Figure 1 ), a large number of flaky and honeycomb structures are formed on the plastic surface after plasma treatment. This indicates that plasma etching effect occurs on the plastic surface during plasma treatment, which can promote the cross-linking, bond breaking and reconstruction process of the plastic surface.
[0057] The surface functional groups of the high-density polyethylene after plasma treatment described in Example 1 are as follows Figure 4 The results of Fourier transform infrared spectroscopy showed that after qualitative analysis, the -1 The signals at 1462 and 1474 cm -1 The absorption peak at 1733 cm-1 can be attributed to the bending deformation of the methylene group. Quantitative analysis shows that the methylene absorption signal of the sample is enhanced after argon plasma treatment. These methylene groups are located at the ends of the polyethylene long chains and the ends of the branches. The increase in their concentration indicates an increase in the dissociation degree of the polyethylene long chains. At the same time, it was observed that the absorption peak at 1733 cm-1 -1 The carbonyl absorbance at 720 and 730 cm-1 was increased after plasma treatment, indicating that the carbonyl concentration on the plastic surface and the dissociation degree of polyethylene long chains increased after argon plasma treatment. -1 The vibration band of 720 cm corresponds to the deformation of the methylene bonding plane in the amorphous and crystalline phases of polyethylene. -1 and 730 cm -1There are differences in the absorption peak intensity at . These changes are related to the difference in the content of amorphous and crystalline phases in polyethylene plastics. Compared with untreated high-density polyethylene, the surface crystallinity of the samples treated with argon plasma increased from 65.44% to 69.44%, respectively. Due to the porous structure of the amorphous regions, these regions are preferentially oxidized and removed. These oxidized areas on the surface of polyethylene plastic particles can easily react with active oxygen species in the plasma, resulting in their rapid consumption, thereby increasing the surface crystallinity of polyethylene. And as Figure 8 As shown, the sol-gel chromatography test results show that compared with the untreated high-density polyethylene plastic sample, the high-density polyethylene plastic treated in Example 1 has a lower degree of polymerization and an average molecular weight, indicating that plasma treatment can promote the depolymerization of plastic particles.
[0058] Example 2
[0059] A method for plasma pretreatment of solid plastics to increase the yield of gaseous hydrocarbon pyrolysis products for resource utilization, wherein each step and the reagents, process parameters and product detection methods used in each step are the same as those in Example 1, except that the carrier gas used in the plasma discharge process in this embodiment is helium.
[0060] Example 3
[0061] A method for plasma pretreatment of solid plastics to increase the yield of gaseous hydrocarbon pyrolysis products for resource utilization, wherein each step and the reagents, process parameters and product detection methods used in each step are the same as those in Example 1, except that the carrier gas used in the plasma discharge process in this embodiment is nitrogen.
[0062] Example 4
[0063] A method for plasma pretreatment of solid plastics to increase the yield of gaseous hydrocarbon pyrolysis products for resource utilization, wherein each step and the reagents, process parameters and product detection methods used in each step are the same as those in Example 1, except that in this embodiment, the second section of the pyrolysis unit (i.e., the lower catalytic conversion layer) is filled with 10 mg of FeNi / Al2O3 supported catalyst.
[0064] Example 5
[0065] A method for plasma pretreatment of solid plastics to increase the yield of gaseous hydrocarbon pyrolysis products for resource utilization, wherein each step and the reagents, process parameters and product detection methods used in each step are the same as those in Example 2, except that in this embodiment, the second section of the pyrolysis unit (i.e., the lower catalytic conversion layer) is filled with 10 mg of FeNi / Al2O3 supported catalyst.
[0066] Example 6
[0067] A method for plasma pretreatment of solid plastics to increase the yield of gaseous hydrocarbon pyrolysis products for resource utilization, wherein each step and the reagents, process parameters and product detection methods used in each step are the same as those in Example 3, except that in this embodiment, the second section of the pyrolysis unit (i.e., the lower catalytic conversion layer) is filled with 10 mg of FeNi / Al2O3 supported catalyst.
[0068] Comparative Example 1
[0069] Commercial high-density polyethylene particles (brand: McLean, CAS number: 9002-88-4, item number: H875017) were crushed and sieved to obtain 60-80 mesh high-density polyethylene particles. They were placed in a constant temperature oven and dried at 80 °C for 10 hours to obtain high-density polyethylene particles that were not treated with plasma. Figure 1 Scanning electron microscopy results show that the surface of high-density polyethylene particles without plasma treatment presents a smooth morphology. Fourier transform infrared spectrum of the comparative example ( Figure 4 , 5 ) shows that the surface of the plastic particles that have not been treated with plasma has methylene functional groups, but the signal intensity is low, indicating that its concentration is lower than the samples described in Examples 1 and 2 after plasma treatment, and no carbonyl functional groups are observed. As shown in 8, the molecular weight distribution curve of the comparative example is located on the left, indicating that its average molecular weight is significantly greater than the sample described in Example 1, indicating that plasma pretreatment can promote the dissociation of plastics. The high-density polyethylene particles that have not been treated with plasma are further pyrolyzed and their pyrolysis products are detected. The pyrolysis and detection conditions refer to the "Performance Detection Experiment" section.
[0070] Comparative Example 2
[0071] A method for pyrolyzing commercial high-density polyethylene plastic particles to achieve resource utilization, wherein each step and the reagents, process parameters and product detection methods used in each step are the same as those in Comparative Example 1, except that during the implementation of this comparative example, the second section of the pyrolysis furnace (i.e., the lower catalytic conversion layer) is filled with 10 mg of FeNi / Al2O3 supported catalyst.
[0072] Comparative Example 3
[0073] A method for plasma pretreatment of solid plastics to achieve resource utilization, wherein each step and the reagents, process parameters and product detection methods used in each step are the same as those in Example 1, except that, in the process of plasma treatment of plastic particles in this comparative example, quartz glass balls are not filled in the plasma discharge cavity of the dielectric barrier discharge plasma reactor.
[0074] Performance testing experiment
[0075] The generation device and detection device for rapid pyrolysis and degradation of plastics are respectively a vertical microreactor (Rx-3050TR, Frontier Laboratory, Japan) and a gas chromatography separation and detection (8890, Agilent, USA) coupling system. The system uses helium as a carrier gas with a flow rate of 156 mL / min. The plastic is the high-density polyethylene particles treated with plasma described in Examples 1 to 6 or the high-density polyethylene particles not treated with plasma in Comparative Examples 1 to 2 or the high-density polyethylene particles treated with plasma in Comparative Example 3 placed in a dielectric barrier discharge reactor not filled with dielectric balls, and the feed is 500 μg. During the reaction, the pyrolysis reaction temperature of the upper layer of the vertical microreactor is 600°C, and the reaction temperature of the lower catalytic conversion layer is 800°C, which is filled with inert quartz wool. During the detection, the gas products of the reaction are first separated by a chromatographic column (113-4362, Agilent) and detected by a thermal conductivity detector, and the reference flow rate is 20 mL / min. The initial temperature of the gas chromatograph column box was 40°C, and the temperature was increased to 280°C at a heating rate of 6°C / min and maintained for 6 min. The quantification of the products produced by the pyrolysis of the plastic was carried out by the external standard method. The pyrolysis products of different embodiments and comparative examples are shown in Table 1 below.
[0076] Table 1 Distribution of plastic pyrolysis products in Examples 1 to 6 and Comparative Examples 1 to 3
[0077]
[0078] Combining the performance test results of Examples 1, 2 and Comparative Example 1 in Table 1, it can be seen that the plastic modified by plasma of the present invention has the characteristics of low degree of polymerization, high crystallinity and rich surface functional groups, which is conducive to the production of a large amount of methane, ethane, propane, ethylene and propylene substances during the pyrolysis of plastics, and increases the yield of pyrolysis gaseous products. Among them, the contents of ethylene, ethane and propylene in high-density polyethylene plastics treated with argon plasma are increased by 19.78%, 46.42% and 8.59% respectively compared with untreated plastics. The yield of gaseous hydrocarbon substances in the pyrolysis products of high-density polyethylene treated with plasma is significantly higher than that of untreated high-density polyethylene in the comparative example. When the catalyst is filled, the plastic treated with plasma shows a higher hydrogen yield. Combining the performance test results of Examples 1 and Comparative Examples 1 and 3 in Table 1, it can be seen that when quartz glass beads are filled in the discharge cavity of the plasma reactor during the plasma pretreatment of plastic particles, a higher yield of gaseous hydrocarbon substances such as methane, ethane, propane, ethylene and propylene can be achieved compared with when quartz glass beads are not filled.
[0079] Example 7
[0080] A dielectric barrier discharge plasma reaction device for pretreating solid plastics in the above-mentioned embodiments 1 to 6 to increase the yield of gaseous hydrocarbon pyrolysis products and realize resource utilization, the structure of which is as follows Fig. 9 As shown: it includes a shell 6 that penetrates from top to bottom, a solid dielectric ball 5, an air inlet 11, an air outlet 12, a first electrode plate (positive electrode) 2, a second electrode plate (ground electrode) 9, a first dielectric plate 4 and a second dielectric plate 7;
[0081] The shell 6 is through-through, with a first dielectric plate 4 disposed on the top and a second dielectric plate 7 disposed on the bottom. The cavity formed by the shell, the first dielectric plate and the second dielectric plate is a discharge cavity. The solid dielectric ball 5 (quartz glass ball) is filled in the discharge cavity.
[0082] The air inlet 11 and the air outlet 12 are located on both sides of the housing 6;
[0083] The first electrode plate 2 is attached to the top of the first dielectric plate 4 , and the second electrode plate 9 is attached to the bottom of the second dielectric plate 7 .
[0084] The dielectric barrier discharge plasma reactor also includes an upper cover 3 and a lower end cover 8; the upper cover 3 is sleeved on the outside of the first electrode plate 2 and screwed to the top of the shell 6, tightly pressing and fixing the first dielectric plate 4 between the shell 6 and the first electrode plate 2; the lower end cover 8 is sleeved on the outside of the second electrode plate 9 and screwed to the bottom of the shell 6, tightly pressing and fixing the second dielectric plate 7 between the shell 6 and the second electrode plate 9.
[0085] The dielectric barrier discharge plasma reaction device further includes upper and lower brackets; the upper bracket 1 is connected and fixed above the first electrode plate 2 , and the lower bracket 10 is connected and fixed below the second electrode plate 9 .
[0086] The dielectric barrier discharge plasma reaction device has upper and lower brackets correspondingly provided with screw holes, and the upper and lower brackets are fastened by bolts 13 to clamp and fix the dielectric barrier discharge plasma reaction device.
[0087] like Fig.10 As shown in the figure, during the plasma treatment of high-density polyethylene plastic, when the reactor is not filled with dielectric balls, only a small amount of discharge pulse signals can be observed at the peak of the current curve. These pulses have low density and high intensity, indicating that the plasma discharge characteristics in the reactor at this time are mainly local discharges. When a reactor filled with glass beads is used, a longer plasma discharge time and a higher discharge density are obtained. The plasma discharge time in a single discharge cycle increases from 14 μs without filling to 33 μs after filling with glass beads, and the current intensity increases from 5.41 mA to 8.77 mA. This shows that filling with glass beads expands the plasma discharge space, thereby achieving a higher density and more uniform plasma filamentary discharge mode, which is beneficial to improve the degree of treatment of plastic particles.
[0088] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for realizing resource recovery by plasma treatment of solid waste plastics, characterized in that: The following steps are involved: (1) Placing plastic particles in a discharge cavity of a dielectric barrier discharge plasma reaction device, performing carrier gas purge at room temperature, and then performing plasma treatment to obtain plasma-treated plastic particles; The discharge cavity of the dielectric barrier discharge plasma reaction device is filled with solid dielectric balls; (2) In an inert gas atmosphere, the plasma-treated plastic particles are pyrolyzed to obtain a mixed product containing gaseous hydrocarbons, thereby realizing the resource utilization of solid waste plastics; Step (1) The depth of the discharge cavity of the dielectric barrier discharge plasma reaction device is 6 to 20 mm, and the interior is filled with solid dielectric spheres, wherein the diameter of the solid dielectric spheres is greater than 2 mm and less than the depth of the discharge cavity; The carrier gas in step (1) is an inert gas; The conditions of the plasma treatment in step (1) are: a discharge power of 5 to 100 W, a carrier gas flow rate of 50 to 100 mL / min, and a plasma treatment time of 5 minutes to 3 hours.
2. According to claim 1, a method for realizing resource recovery by plasma treatment of solid waste plastics, characterized in that: The dielectric barrier discharge plasma reaction device in step (1) is a dielectric barrier discharge plasma reactor with a double-layer dielectric flat plate structure.
3. According to claim 1, a method for realizing resource recovery by plasma treatment of solid waste plastics, characterized in that: The material of the solid dielectric sphere in step (1) is at least one of ceramic and glass.
4. The method for realizing resource recovery by plasma treatment of solid waste plastics according to claim 1, characterized in that: The material of the solid dielectric sphere in step (1) is at least one of alumina ceramic, zirconia ceramic, barium titanate ceramic and quartz glass; The carrier gas in step (1) is at least one of argon, helium and nitrogen; The conditions of the plasma treatment in step (1) are: discharge power of 20 W, carrier gas flow rate of 50 mL / min, and plasma treatment time of 1 hour.
5. The method for realizing resource recovery by plasma treatment of solid waste plastics according to claim 1, characterized in that: The plastic in step (1) is a general-purpose plastic, specifically at least one of PVC, PE, PP, PS and ABS; The plastic particles in step (1) need to be cleaned, crushed and sieved before being treated with plasma; the sieving is to a size of 20 to 100 meshes.
6. The method for realizing resource recovery by plasma treatment of solid waste plastics according to claim 1, characterized in that: The inert gas in step (2) is at least one of argon, helium and nitrogen; The pyrolysis conditions of step (2) are: carrier gas flow rate of 100 to 500 mL / min, temperature of 500 to 800 °C, and pyrolysis time of 1 to 30 minutes.
7. The method for realizing resource recovery by plasma treatment of solid waste plastics according to claim 1, characterized in that: After pyrolysis in step (2), a mixed product containing gaseous hydrocarbons is obtained, which is further heated and catalytically converted into hydrogen under the action of a catalyst; The temperature of the heating catalysis is 800-1000°C.
8. A dielectric barrier discharge plasma reaction device for assisting the method according to claims 1 to 7, characterized in that: It includes a shell that penetrates from top to bottom, a solid dielectric ball, an air inlet, an air outlet, a first electrode plate, a second electrode plate, a first dielectric plate and a second dielectric plate; The shell is through-through, with a first dielectric plate on the top and a second dielectric plate on the bottom. The cavity formed by the shell, the first dielectric plate and the second dielectric plate is a discharge cavity. The solid dielectric ball is filled in the discharge cavity. The air inlet and the air outlet are located on both sides of the shell; The first electrode plate is attached above the first dielectric plate, and the second electrode plate is attached below the second dielectric plate.
9. The dielectric barrier discharge plasma reaction device according to claim 8, characterized in that: Also includes an upper cover and a lower end cover; The upper cover is sleeved on the outside of the first electrode plate and is screwed to the top of the shell to tightly press and fix the first dielectric plate between the shell and the first electrode plate; The lower end cover is sleeved outside the second electrode plate and screwed to the bottom of the shell to tightly press and fix the second dielectric plate between the shell and the second electrode plate.
10. The dielectric barrier discharge plasma reaction device according to claim 8, characterized in that: It also includes an upper bracket and a lower bracket; the upper bracket is connected and fixed above the first electrode plate, and the lower bracket is connected and fixed below the second electrode plate; The upper bracket and the lower bracket are correspondingly provided with screw holes, and the upper bracket and the lower bracket are fastened by bolts to clamp and fix the dielectric barrier discharge plasma reaction device.
Citation Information
Patent Citations
Methods and compositions for production of green mortar
US20220402818A1
Process for recycling organic materials with the production of carbon nanotubes
WO2009081362A1
